PSYCHOLOGICAL ASPECTS OF MORAL DEVELOPMENT: HISTORY AND RECENT STUDIES - Trups-Kalne, Ingrīda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The aim of the study is to analyse psychological aspects of  moral development by assessing studies on cognitive rational theory, as well as to learn about the most recent studies on the socially intuitive and evolutionary paradigm of morality. The study analyses the views of Piaget, Kohlberg, Lind, Shweder, Haidt, Joseph, Hamlin, Wynn, Bloom and others on cultural differences of the content of morality, process and mechanisms of moral development, as well as endogenous and environmental factors affecting development. The study led to conclusion that general understanding about morality is innate to a human being and that morality is the core of personality, which helps people to work and live together in a community.